Origins and structure of social and political attitudes: insights from personality system theory and behavioural genetics - Lewis, Gary J. (The University of Edinburgh, 2012)
People differ, often strikingly, in their views on desired social structures and processes. For example, while some value ethnic diversity in their society, others believe non -indigenous individuals (whatever that might mean) should be repatriated to their land of origin. Similarly, whereas some believe religion should play no role in determining social policy, others strongly advocate the importance of living according to religious scripture, including at a social level. This variation in attitudes, and its implication for societal cohesion, has made research on the origins of social and political attitudes of enduring interest to psychologists, sociologists, political scientists, among many others.

The goal of the current thesis was to extend work in this literature in two key ways: Firstly, I examined whether political attitudes can be understood within a personality system model. This work addresses previous mixed results on the links of basic personality traits to political conservatism. In Chapter 3, I test predictions from this model; namely, that direct influences on political behaviour flow from moral values, with personality mostly acting indirectly via these moral values, rather than directly affecting political attitudes. Findings from two studies (published as Lewis & Bates, 2011a) supported these predictions suggesting that the new model helps explain inconsistencies in previous research attempting to link personality to political orientation that have not included the intermediary level of values.

Secondly, I examined the genetic architecture of social attitudes constructs in three separate studies. Chapter 4 addressed whether in -group favouritism reflects heritable effects, and, secondly, whether race -favouritism was accounted for broad or specific genetic effects. Results indicated that a common biological mechanism exists facilitating generalised favouritism, with evidence for additional genetic effects specific to each form of group favouritism. These findings (published as Lewis & Bates, 2010) suggest that (at least) at the genetic level, race favouritism is multiply determined.

In Chapter 5, I examined whether prosocial obligations across the domains of welfare, work, and civic obligation share a common genetic basis, or reflect specific heritable components (published as Lewis & Bates, 2011b). In females, results indicated the existence of a common heritable factor underlying each of these prosocial obligations. In males, a prosocial factor was also observed; familial effects (genetic and shared -environment effects were indistinguishable) influenced this general mechanism. At the domain -specific level, modest genetic effects were observed in females for civic and work obligations, with shared - environment effects influencing welfare obligations. In males, genetic influences were observed for welfare obligation, with unique -environments affecting work and civic duty.

Finally, in Chapter 6, I present work examining the genetic architecture of religious belief. Although genetic factors are known to influence strength of religious belief, the psychological mechanism(s) through which this biological influence is manifest are presently unknown. Two non -theological constructs - 1) need for community integration and 2) need for existential certainty - were hypothesised to account for the genetic effects on religiosity. The results supported this hypothesis, with genetic influences on these traits wholly accounting for the heritable basis of religiosity, suggesting that religion "re- uses" systems involved in meeting both social and existential needs.